Quantification and modeling of non-point source pollution in residential, commercial and industrial catchments - Chow, Ming Fai, 1983-; Zulkifli Yusop, supervisor; Fakulti Kejuruteraan Awam (2011)
Thesis (Ph.D (Awam - Hidrologi dan Sumber Air)) - Universiti Teknologi Malaysia, 2011